2018
DOI: 10.1186/s12940-018-0439-1
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among workers exposed to asbestos at the shipyard of Genoa, Italy: a 55 years follow-up

Abstract: BackgroundExposure to asbestos remains a global issue due to its massive use in the twentieth century and its long environmental persistence. Exposure to asbestos still occurs during dismantling of ships and vessels, buildings renovation, mining operations, and is reported in developing countries. Current estimate report exposure of hundreds of million people in occupational settings in countries where its use remains unregulated.MethodsWe conducted a historical prospective cohort mortality study aimed at esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
0
5
0
3
Order By: Relevance
“…A recently published mortality study on a comparable cohort of Genoa shipyard workers identified 103 pleural cancer versus 399 LC deaths (90 in excess of expectation). 9 Accordingly, whereas excess LC deaths were (roughly) as many as pleural cancer (or, equivalently, MPM) deaths, the total LC number was about 4 times as high. Other studies found relatively lower ratios of LC to MPM deaths and incidence: about 3 to 1 and 2 to 1, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…A recently published mortality study on a comparable cohort of Genoa shipyard workers identified 103 pleural cancer versus 399 LC deaths (90 in excess of expectation). 9 Accordingly, whereas excess LC deaths were (roughly) as many as pleural cancer (or, equivalently, MPM) deaths, the total LC number was about 4 times as high. Other studies found relatively lower ratios of LC to MPM deaths and incidence: about 3 to 1 and 2 to 1, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…A study of 2644 mesothelioma cases with asbestos exposure history collected by the Italian Mesothelioma Register (ReNaM) found a median latency of 44.6 years (6–84 years for males and 9–84 years for females) [ 12 ]. Finally, Merlo et al found a minimum latency of 9 years in shipyard workers in Genova [ 57 ], and Lacourt reported a latency range of 7–61 years [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…), and chemical substances ( 8 , 9 ). Furthermore, port workers may be exposed to asbestos in the course of their work ( 10 ). For a long time, asbestos was widely used in various fields (maritime, industrial, military and construction sectors, etc.…”
Section: Introductionmentioning
confidence: 99%